The new Silk Road leads through the Arab Peninsula : mastering global business and innovation - Visvizi, Anna; Lytras, Miltiadis D.; Alhalabi, Wadee; Zhang, Xi (Emerald Publishing Limited, 2019)
Building on the tradition, promises and advances brought by the historical Silk Road, the Belt and Road Initiative launched by Chinese authorities in 2013 has the potential to re-draw the map of checks and balances in the global economy. The New Silk Road leads through the Arab Peninsula: Mastering Global Business and Innovationoffers an in-depth inquiry into the origins, implications, opportunities and synergies that China's Belt and Road Initiative creates for stakeholders in both Asia and the Arab World.Acclaimed academics, practitioners and experts contribute to a fascinating overview of critical issues that emerge along the New Silk Road. Chapters address issues such as dispute resolution, the geopolitics of international business, the enabling role of sophisticated technologies, approaches to innovation promotion and cross-cultural collaboration. Case-studies featuring specific businesses and industries operating in the Belt and Road context further add to the empirical focus that this book offers.An essential resource for graduate and executive education in a range of fields, including international business, international political economy, strategic management, and appliedcomputer science, this volume will also serve as an illuminating study for anyone interested in contemporary global affairs.
Prelims -- Chapter 1: The belt and road initiative: strategy, collaboration, innovation -- Chapter 2: The spirit of Silk Road: the impact of medieval ChineseArab relations on the contemporary bilateral SinoArab relations -- Chapter 3: The past, the present, and the future of the new Silk Road: China as a leader or a free-rider in international relations -- Chapter 4: Dispute resolution along the belt and road initiative -- Chapter 5: The state of innovation dimensions in the GCC countries: past development and the future ahead -- Chapter 6: Building ICT knowledge capacity for female entrepreneurship for sustainable socio-economic growth in the Middle East -- Chapter 7: The analysis of "online Silk Road" from the perspective of big data -- Chapter 8: A framework for the competitive intelligence service system for strategic emerging industries in China -- Chapter 9: An overview of artificial intelligence research and development in China -- Chapter 10: Introduction to Chinese knowledge graphs and their applications -- Chapter 11: Pakistan's role in the new Silk route: belt and road initiative -- Chapter 12: The Chinese and the Saudi new energy models transcending into regional energy cooperation -- Chapter 13: Cluster analysis and overseas warehouse assignment of Chinese smartphones under "the belt and road" initiative -- Chapter 14: A research on the development trend of knowledge payment based on Zhihu -- Chapter 15: Conclusions -- Index.
Includes index.
Print version record
Keywords: Trade routes; China -- Foreign economic relations; Middle East -- Economic conditions; Business & Economics -- International -- Economics; International business